2017
DOI: 10.1111/jdv.14365
|View full text |Cite
|
Sign up to set email alerts
|

Psoriasis in patients with mycosis fungoides: a clinicopathological study of 25 patients

Abstract: Our results support the opinion that the association between psoriasis and MF does exist. It is most possibly related to the chronic lymphocyte stimulation that occurs during psoriasis that eventually leads to a dominant clone and the evolution to CTCL. Our study suggests that apart from cases of early MF, which are being indeed misdiagnosed as psoriasis, there is another group of patients, where psoriasis truly coexists with - or even progresses to - MF.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
26
0
4

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(31 citation statements)
references
References 15 publications
1
26
0
4
Order By: Relevance
“…The comorbidity of psoriasis and MF has previously been reported . We have already published our experience in this topic in a series of 25 patients, which seems to remain one of the largest cohorts to date .…”
Section: Discussionmentioning
confidence: 92%
“…The comorbidity of psoriasis and MF has previously been reported . We have already published our experience in this topic in a series of 25 patients, which seems to remain one of the largest cohorts to date .…”
Section: Discussionmentioning
confidence: 92%
“…These scenarios challenge the current state of knowledge as psoriasiform MF has been described, emphasizing the link or the coexistence of these two dermatoses. The association of MF and psoriasis recently reported in 25 patients with psoriasis among 321 patients with MF, raises the combined hypotheses of overlapping forms of MF and psoriasis, influence of immunosuppressive agents and the same pathological pathways involving T helper 17. The predominance of patients using biologics for psoriasis in two recent series (less obvious in ours) suggests the aggravating or revealing role of biologics on pre‐existing MF.…”
Section: Cutaneous Lymphoma During Treatment With Biologics: Data Fromentioning
confidence: 95%
“…The link between psoriasis, MF, and anti‐TNF‐α agents remains elusive . The pathogenesis of both psoriasis and MF is strictly related to the abnormal function of skin‐homing T‐cells, specifically Th1 and Th17 populations; and several studies have identified an increased relative risk for lymphomas, including CTCLs, in psoriatic patients .…”
mentioning
confidence: 99%
“…The link between psoriasis, MF, and anti‐TNF‐α agents remains elusive . The pathogenesis of both psoriasis and MF is strictly related to the abnormal function of skin‐homing T‐cells, specifically Th1 and Th17 populations; and several studies have identified an increased relative risk for lymphomas, including CTCLs, in psoriatic patients . The explanation underlying these results may lie on the chronic lymphocyte‐driven inflammatory state of psoriasis plus the use of immunosuppressive therapies, such as anti‐TNF‐α agents, helping select a malignant T‐cell clone, provoking the development of CTCL …”
mentioning
confidence: 99%
See 1 more Smart Citation